Next Generation EU. An opportunity for a stronger Europe (Cultura Económica, 2020)
The agreement reached by the European Council in July 2020 to support the recovery of the countries struck by the COVID 19 crisis was a landmark event. The Next Generation EU and 2021-2027 EU budget were approved, two closely related instruments implementing a strategy designed to stimulate both the reactivation of the national economies and contemporaneously, the sustainable development of Europe. The action taken constitutes an extraordinary effort, due to the volume of the financial resources involved, to be divided amongst the countries according to the various levels of need, based on their respective national recovery and resilience plans. The most important innovation was the decision to collectively incur debt to finance the aid package, and to pay back part of the amount owed with new «own resources», that is, new European taxes/duties (e.g. the carbon and web taxes). In this way we are moving towards a European fiscal system. Despite this, the negotiation process that led to the agreement highlighted pre-existing fractures that have not been repaired: some among the countries themselves (above all the «frugal» Northern nations and those of the South) and others between intergovernmental Europe and the Europe of the EU policies. The European Parliament, for its part, is demanding a budget increase in a bid to avoid sacrificing a number of key EU programmes. Although tension is running high, and the many difficulties threatening the final decisions that would implement the Next Generation EU, there appears to be no way of backing out. The elements at stake not only include the ability to overcome the current social-economic crisis, but also the European integration plan and the EU’s position on the international scene. Two factors will prove decisive in the next few years: the ability of the European Commission to adequately steer and oversee the national plans, and the will of the governments to setting out a reform and investment agenda, as well as an efficient management of the funds.
Keywords: EUROPEAN UNION; NEXT GENERATION EU; SOCIAL AND ECONOMIC RECOVERY FROM THE COVID-19 CRISIS; EUROPEAN INTEGRATION PROCESS